The Plot-Compositional Structure of the Play by M. Gorky of the 30s Of the Xx Century (“Egor Bulychov and Others”, “Dostigaev and Others”) - Isayeva Yu.P. (Peerian Journals Publishing, 2022)
The article deals with the plot-compositional structure of the plays of the 30s of the XX century. The dramaturgy of this period bears all the hallmarks of a new European drama. The depiction of historical events is combined in them with in-depth attention to the inner world of a person; acute social and moral problems destroy the usual stereotypes of family and everyday drama. The voice of the author sounds in the works simultaneously with the voice of history, creating a carefully hidden background.
Keywords: Gorky; dramaturgy; theater; innovation